Formation of compressed flat electron beams with high transverse-emittance ratios - J. Zhu; P. Piot; D. Mihalcea; C. R. Prokop (Physical Review Special Topics. Accelerators and Beams, 2014)
Flat beams—beams with asymmetric transverse emittances—have important applications in novel light-source concepts and advanced-acceleration schemes and could possibly alleviate the need for damping rings in lepton colliders. Over the last decade, a flat beam generation technique based on the conversion of an angular-momentum-dominated beam was proposed and experimentally tested. In this paper we explore the production of compressed flat beams. We especially investigate and optimize the flat beam transformation for beams with substantial fractional energy spread. We use as a simulation example the photoinjector of Fermilab’s Advanced Superconducting Test Accelerator. The optimizations of the flat beam generation and compression at Advanced Superconducting Test Accelerator were done via start-to-end numerical simulations for bunch charges of 3.2 nC, 1.0 nC, and 20 pC at ∼37  MeV. The optimized emittances of flat beams with different bunch charges were found to be 0.25  μm (emittance ratio is ∼400), 0.13   μm, 15 nm before compression, and 0.41  μm, 0.20  μm, 16 nm after full compression, respectively, with peak currents as high as 5.5 kA for a 3.2-nC flat beam. These parameters are consistent with requirements needed to excite wakefields in asymmetric dielectric-lined waveguides or produce significant photon flux using small-gap micro-undulators.